Total and partial posterior quadrant disconnection for medically refractory epilepsy: A systematic review. (October 2021) - Markosian, Christopher; Dodson, Vincent; Zhang, Helen J.; Mahalingam, Rajeshwari S.; Geller, Eric B.; Tomycz, Luke D.
Highlights: Total or partial posterior quadrant disconnection (PQD) is a surgical treatment option for medically refractory epilepsy (MRE). Overall, 75% of patients undergoing total PQD achieved seizure freedom compared to 63% for partial PQD. Positron emission tomography (PET) / single-photon emission computed tomography (SPECT) more often accompanied total PQD. Wada / functional magnetic resonance imaging (fMRI) and intracranial electroencephalography (icEEG) more often accompanied partial PQD. Concordant interictal and ictal electroencephalography (EEG) findings were predictive of seizure freedom. Abstract: Purpose: Posterior quadrant disconnection (PQD) is a surgical procedure for medically refractory epilepsy (MRE) involving diffuse regions of the temporo-parieto-occipital lobes. We sought to compare factors and efficacy according to PQD extent. Methods: We performed a systematic review of the literature reporting the use of PQD since 2004. We analyzed various characteristics of pooled cases, including the role of preoperative studies in patient selection, intraoperative techniques, and outcomes. Results: Our review of 137 patients from nine studies revealed 66% undergoing total PQD and 34% undergoing partial PQD. Interictal electroencephalography (EEG) findings were predominantly characterized as lateralized for total PQD (56%) and localized within the ipsilateral posterior quadrant in patients undergoing partial PQD (53%). Metabolic functional studies [positron emission tomography (PET) or ictal single-photon emission computed tomography (SPECT)] played a role in surgical decision-making in 42% of patients who underwent total PQD. Wada and/or functional magnetic resonance imaging (fMRI) was more often utilized for partial PQD (22%) than total PQD (3%) as was intracranial electroencephalography (icEEG) (30% versus 13%, respectively). Overall, 75% of total PQD patients achieved seizure freedom [defined as Engel I or International League Against Epilepsy (ILAE) Class 1 outcome] in comparison to 63% of partial PQD patients (p = .078). New visual field deficits were seen in 12% and new or worsened hemiparesis in 6%. For patients in either cohort, concordance of interictal and ictal EEG findings was found to be predictive of seizure freedom (p = .048). Conclusion: Both total and partial PQD represent effective alternatives for managing patients with MRE whose seizure onset zone (SOZ) involves a diffuse region within the posterior quadrant. While PET and/or SPECT frequently aided in the decision to proceed with total PQD, patients who underwent a tailored, partial multilobar resection were more likely to undergo Wada and/or fMRI testing as well as stage I icEEG studies.